2007
DOI: 10.1002/hyp.6526
|View full text |Cite
|
Sign up to set email alerts
|

Use of mixed bivariate distributions for deriving inter‐station correlation coefficients of rain rate

Abstract: Abstract:Even though rain rate is notorious for its spatial and temporal intermittency, its effect on the second-order statistics of rain rate, especially the inter-station correlation coefficients, has not been intensively evaluated before. This study has derived and compared the inter-station correlation coefficient of rain rate for three cases of data: (1) only the positive measurements at both locations; (2) the positive measurements at either one or both locations; (3) all the measurements including zero … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Especially the bivariate mixed log-normal distribution defined by Shimizu and Sagae (1990) and Shimizu (1993) was adopted for the bivariate analysis in this study. Detailed procedure of applying this bivariate distribution function can also be found in Ha and Yoo (2006).…”
Section: Derivation Of Spatial Correlation Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially the bivariate mixed log-normal distribution defined by Shimizu and Sagae (1990) and Shimizu (1993) was adopted for the bivariate analysis in this study. Detailed procedure of applying this bivariate distribution function can also be found in Ha and Yoo (2006).…”
Section: Derivation Of Spatial Correlation Functionsmentioning
confidence: 99%
“…Introducing the concept of bivariate mixed distribution function makes it possible to derive the spatial correlation functions analytically (Kedem et al 1990;Ha and Yoo 2006), which also makes it possible to show how the portion of zero measurements and the spatial variability of positive measurements change the spatial correlation structure of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Yoo and Ha (2007) and Ha and Yoo (2007) have shown that zero measurements cannot be used for characterizing a rainfall field from rain gauge measurements because they decrease the spatial variability of the data and produce a high variability of the correlation between pairs of time series, with several abnormally high estimates. However, considering pairs of radar and gauge rainfall series, zero radar rainfall estimates occur especially at far ranges, when the radar returns from precipitation can be quite close to the minimum detectable signal due to range degradation or attenuation.…”
Section: Radar Datamentioning
confidence: 99%
“…They evaluated the effect of time-scale range, inter-storm variability, and rainfall intensity. Furthermore, to characterize the spatiotemporal variability of the rainfall intensity, Ha and Yoo (2007) used the inter-station correlation coefficient of the rainfall intensity derived from the mixed bivariate rainfall distribution. Based on the use of inter-gauge correlation, the purpose of this study is to assess a rain-gauge distribution to increase capability and efficiency in rainfall measurements.…”
Section: Introductionmentioning
confidence: 99%